Nudix hydrolases degrade protein-conjugated ADP-ribose - Daniels, Casey M. (Sci Rep, 2015)
ADP-ribosylation refers to the transfer of the ADP-ribose group from NAD(+) to target proteins post-translationally, either attached singly as mono(ADP-ribose) (MAR) or in polymeric chains as poly(ADP-ribose) (PAR). Though ADP-ribosylation is therapeutically important, investigation of this protein modification has been limited by a lack of proteomic tools for site identification. Recent work has demonstrated the potential of a tag-based pipeline in which MAR/PAR is hydrolyzed down to phosphoribose, leaving a 212 Dalton tag at the modification site. While the pipeline has been proven effective by multiple groups, a barrier to application has become evident: the enzyme used to transform MAR/PAR into phosphoribose must be purified from the rattlesnake Crotalus adamanteus venom, which is contaminated with proteases detrimental for proteomic applications. Here, we outline the steps necessary to purify snake venom phosphodiesterase I (SVP) and describe two alternatives to SVP—the bacterial Nudix hydrolase EcRppH and human HsNudT16. Importantly, expression and purification schemes for these Nudix enzymes have already been proven, with high-quality yields easily attainable. We demonstrate their utility in identifying ADP-ribosylation sites on Poly(ADP-ribose) Polymerase 1 (PARP1) with mass spectrometry and discuss a structure-based rationale for this Nudix subclass in degrading protein-conjugated ADP-ribose, including both MAR and PAR.